Prolonged neoadjuvant chemotherapy without radiation versus total neoadjuvant therapy for locally advanced rectal cancer: A propensity score matched study - Zhao, Xuan; Han, Peiyi; Zhang, Luyang; Ma, Junjun; Dong, Feng; Zang, Lu; He, Zirui; Zheng, Minhua (Frontiers in Oncology, 2022)
Background Although neoadjvuant chemoradiotherapy (CRT) improves the local control rate of locally advanced rectal cancer (LARC), it fails to significantly improve disease-free survival (DFS) and overall survival (OS). We explored the efficacy of prolonged neoadjuvant chemotherapy (pNCT) without radiation and compared this schema with total neoadjuvant therapy (TNT). Material and methods Patients diagnosed with LARC and received TNT (4 cycles of induction CapeOX/FOLFOX followed with CRT) or pNCT (6~8 cycles of CapeOX/FOLFOX) between June 2016 and October 2021 were retrospective analyzed. All patients underwent total mesorectal excision (TME). A 1:1 propensity score match was performed to adjust baseline potential confounders. The tumor response, toxicity, recurrence-free survival (RFS) and OS were observed. Results A total of 184 patients with 92 patients in each group were finally enrolled. The median follow-up time was 35 months. TNT showed better pathological complete response (pCR) rate (25.0% vs 16.3%) and objective regression rate (73.9% vs 59.8%) than pNCT. TNT and pNCT produce similar 3-year RFS and OS rates in patients with mid-to-upper rectal cancer. TNT was associated with improved tumor responsiveness in all patients and improved 3-year RFS rates in those with low rectal cancer. Conclusion pNCT is an option for patients with mid-to-upper rectal cancer, but radiation is still necessary for low rectal cancer. To determine optimal schema for neoadjuvant therapy and patient selection, additional randomized controlled studies are needed.